\(lim\frac{2+2^2+2^3+...+2^n}{5+5^2+5^3+...+5^n}\)
Tính các giới hạn sau:
a) \(\lim \frac{{2{n^2} + 6n + 1}}{{8{n^2} + 5}}\)
b) \(\lim \frac{{4{n^2} - 3n + 1}}{{ - 3{n^3} + 5{n^2} - 2}}\);
c) \(\lim \frac{{\sqrt {4{n^2} - n + 3} }}{{8n - 5}}\);
d) \(\lim \left( {4 - \frac{{{2^{n + 1}}}}{{{3^n}}}} \right)\)
e) \(\lim \frac{{{{4.5}^n} + {2^{n + 2}}}}{{{{6.5}^n}}}\)
g) \(\lim \frac{{2 + \frac{4}{{{n^3}}}}}{{{6^n}}}\).
a) \(\lim \frac{{2{n^2} + 6n + 1}}{{8{n^2} + 5}} = \lim \frac{{{n^2}\left( {2 + \frac{6}{n} + \frac{1}{{{n^2}}}} \right)}}{{{n^2}\left( {8 + \frac{5}{{{n^2}}}} \right)}} = \lim \frac{{2 + \frac{6}{n} + \frac{1}{n}}}{{8 + \frac{5}{n}}} = \frac{2}{8} = \frac{1}{4}\)
b) \(\lim \frac{{4{n^2} - 3n + 1}}{{ - 3{n^3} + 6{n^2} - 2}} = \lim \frac{{{n^3}\left( {\frac{4}{n} - \frac{3}{{{n^2}}} + \frac{1}{{{n^3}}}} \right)}}{{{n^3}\left( { - 3 + \frac{6}{n} - \frac{2}{{{n^3}}}} \right)}} = \lim \frac{{\frac{4}{n} - \frac{3}{{{n^2}}} + \frac{1}{{{n^3}}}}}{{ - 3 + \frac{6}{n} - \frac{2}{{{n^3}}}}} = \frac{{0 - 0 + 0}}{{ - 3 + 0 - 0}} = 0\).
c) \(\lim \frac{{\sqrt {4{n^2} - n + 3} }}{{8n - 5}} = \lim \frac{{n\sqrt {4 - \frac{1}{n} + \frac{3}{{{n^2}}}} }}{{n\left( {8 - \frac{5}{n}} \right)}} = \frac{{\sqrt {4 - 0 + 0} }}{{8 - 0}} = \frac{2}{8} = \frac{1}{4}\).
d) \(\lim \left( {4 - \frac{{{2^{{\rm{n}} + 1}}}}{{{3^{\rm{n}}}}}} \right) = \lim \left( {4 - 2 \cdot {{\left( {\frac{2}{3}} \right)}^{\rm{n}}}} \right) = 4 - 2.0 = 4\).
e) \(\lim \frac{{{{4.5}^{\rm{n}}} + {2^{{\rm{n}} + 2}}}}{{{{6.5}^{\rm{n}}}}} = \lim \frac{{{{4.5}^{\rm{n}}} + {2^2}{{.2}^{\rm{n}}}}}{{{{6.5}^{\rm{n}}}}} = \lim \frac{{{5^n}.\left[ {4 + 4.{{\left( {\frac{2}{5}} \right)}^{\rm{n}}}} \right]}}{{{{6.5}^n}}} = \lim \frac{{4 + 4.{{\left( {\frac{2}{5}} \right)}^{\rm{n}}}}}{6} = \frac{{4 + 4.0}}{6} = \frac{2}{3}\).
g) \(\lim \frac{{2 + \frac{4}{{{n^3}}}}}{{{6^{\rm{n}}}}} = \lim \left( {2 + \frac{4}{{{{\rm{n}}^3}}}} \right).\lim {\left( {\frac{1}{6}} \right)^{\rm{n}}} = \left( {2 + 0} \right).0 = 0\).
Tính các giới hạn sau:
a) \(\lim \frac{{5n + 1}}{{2n}};\)
b) \(\lim \frac{{6{n^2} + 8n + 1}}{{5{n^2} + 3}};\)
c) \(\lim \frac{{\sqrt {{n^2} + 5n + 3} }}{{6n + 2}};\)
d) \(\lim \left( {2 - \frac{1}{{{3^n}}}} \right);\)
e) \(\lim \frac{{{3^n} + {2^n}}}{{{{4.3}^n}}};\)
g) \(\lim \frac{{2 + \frac{1}{n}}}{{{3^n}}}.\)
a) \(\lim \frac{{5n + 1}}{{2n}} = \lim \frac{{5 + \frac{1}{n}}}{2} = \frac{{5 + 0}}{2} = \frac{5}{2}\)
b) \(\lim \frac{{6{n^2} + 8n + 1}}{{5{n^2} + 3}} = \lim \frac{{6 + \frac{8}{n} + \frac{1}{{{n^2}}}}}{{5 + \frac{3}{{{n^2}}}}} = \frac{{6 + 0 + 0}}{{5 + 0}} = \frac{6}{5}\)
c) \(\lim \frac{{\sqrt {{n^2} + 5n + 3} }}{{6n + 2}} = \lim \frac{{\sqrt {1 + \frac{5}{n} + \frac{3}{{{n^2}}}} }}{{6 + \frac{2}{n}}} = \frac{{\sqrt {1 + 0 + 0} }}{{6 + 0}} = \frac{1}{6}\)
d) \(\lim \left( {2 - \frac{1}{{{3^n}}}} \right) = \lim 2 - \lim {\left( {\frac{1}{3}} \right)^n} = 2 - 0 = 0\)
e) \(\lim \frac{{{3^n} + {2^n}}}{{{{4.3}^n}}} = \lim \frac{{1 + {{\left( {\frac{2}{3}} \right)}^n}}}{4} = \frac{{1 + 0}}{4} = \frac{1}{4}\)
g) \(\lim \frac{{2 + \frac{1}{n}}}{{{3^n}}}\)
Ta có \(\lim \left( {2 + \frac{1}{n}} \right) = \lim 2 + \lim \frac{1}{n} = 2 + 0 = 2 > 0;\lim {3^n} = + \infty \Rightarrow \lim \frac{{2 + \frac{1}{n}}}{{{3^n}}} = 0\)
1) lim \(\frac{3n^2+5n+4}{2-n^2}\)
2) lim \(\frac{2n^3-4n^2+3n+7}{n^3-7n+5}\)
3) lim \(\left(\frac{2n^3}{2n^2+3}+\frac{1-5n^2}{5n+1}\right)\)
4) lim \(\frac{1+3^n}{4+3^n}\)
5) lim \(\frac{4.3^n+7^{n+1}}{2.5^n+7^n}\)
1.
\(\lim \frac{3n^2+5n+4}{2-n^2}=\lim \frac{\frac{3n^2+5n+4}{n^2}}{\frac{2-n^2}{n^2}}=\lim \frac{3+\frac{5}{n}+\frac{4}{n^2}}{\frac{2}{n^2}-1}=\frac{3}{-1}=-3\)
2.
\(\lim \frac{2n^3-4n^2+3n+7}{n^3-7n+5}=\lim \frac{\frac{2n^3-4n^2+3n+7}{n^3}}{\frac{n^3-7n+5}{n^3}}=\lim \frac{2-\frac{4}{n}+\frac{3}{n^2}+\frac{7}{n^3}}{1-\frac{7}{n^2}+\frac{5}{n^3}}=\frac{2}{1}=2\)
3.
\(\lim (\frac{2n^3}{2n^2+3}+\frac{1-5n^2}{5n+1})=\lim (n-\frac{3n}{2n^2+3}+\frac{1}{5}-n-\frac{1}{5n+1})\)
\(=\frac{1}{5}-\lim (\frac{3n}{2n^2+3}+\frac{1}{5n+1})=\frac{1}{5}-\lim (\frac{3}{2n+\frac{3}{n}}+\frac{1}{5n+1})=\frac{1}{5}-0=\frac{1}{5}\)
4.
\(\lim \frac{1+3^n}{4+3^n}=\lim (1-\frac{3}{4+3^n})=1-\lim \frac{3}{4+3^n}=1-0=1\)
5.
\(\lim \frac{4.3^n+7^{n+1}}{2.5^n+7^n}=\lim \frac{\frac{4.3^n+7^{n+1}}{7^n}}{\frac{2.5^n+7^n}{7^n}}\)
\(=\lim \frac{4.(\frac{3}{7})^n+7}{2.(\frac{5}{7})^n+1}=\frac{7}{1}=7\)
P2= lim\(\frac{\sqrt{n+1}}{\sqrt{n}+1}\)
M1= lim\(\frac{1+2+3+...+n}{^{ }n^2+2}\)
A5= lim\(\frac{\left(4-2n\right)^3\left(7n^2+1\right)^5}{\left(n^4+n^3-1\right)^2\left(4-5^5\right)}\)
\(lim\left(\sqrt[3]{n-n^3}+\sqrt{n^2+3n}\right)\)
\(lim\left(\sqrt{n-2\sqrt{n}}-\sqrt{n+4}\right)\)
\(lim\left(\sqrt[3]{3n^2+n^3}-n\right)\)
\(lim\left(\sqrt[3]{n^3+6n}-\sqrt{n^2-4n}\right)\)
\(lim\frac{-3^{n+1}+4^{n+1}}{5.3^n+3.2^{2n-1}}\)
\(lim\left(\frac{3^{2n}-5^{n+1}+7^{n+1}}{3^{n+2}+5^n+2^{3n+2}}\right)\)
\(lim\left(\frac{6^{n+1}+3^{2n+5}}{3^{2n+3}-2^{2n-1}}\right)\)
a/ \(lim\left(\sqrt[3]{n-n^3}+n+\sqrt{n^2+3n}-n\right)\)
\(=lim\left(\frac{n}{\sqrt[3]{\left(n-n^3\right)^2}-n\sqrt[3]{\left(n-n^3\right)}+n^2}+\frac{3n}{\sqrt{n^2+3n}+n}\right)\)
\(=lim\left(\frac{1}{\sqrt[3]{n^3+2n+\frac{1}{n}}+\sqrt[3]{n^3-n}+n}+\frac{3}{\sqrt{1+\frac{3}{n}}+1}\right)=0+\frac{3}{1+1}=\frac{3}{2}\)
b/ \(lim\left(\frac{-2\sqrt{n}-4}{\sqrt{n-2\sqrt{n}}+\sqrt{n+4}}\right)=lim\left(\frac{-2-\frac{4}{\sqrt{n}}}{\sqrt{1-\frac{2}{\sqrt{n}}}+\sqrt{1+\frac{4}{n}}}\right)=-\frac{2}{1+1}=-1\)
c/ \(lim\left(\frac{3n^2}{\sqrt[3]{n^6+6n^5+9n^4}+\sqrt[3]{n^6+3n^5}+n^2}\right)=lim\left(\frac{3}{\sqrt[3]{1+\frac{6}{n}+\frac{9}{n^2}}+\sqrt[3]{1+\frac{3}{n}}+1}\right)=\frac{3}{3}=1\)
d/ \(lim\left(\sqrt[3]{n^3+6n}-n+n-\sqrt{n^2-4n}\right)=lim\left(\frac{6n}{\sqrt[3]{n^6+12n^4+36n^2}+\sqrt[3]{n^6+6n^4}+n^2}+\frac{4n}{n+\sqrt{n^2-4n}}\right)\)
\(=lim\left(\frac{6}{\sqrt[3]{n^3+12n+\frac{36}{n}}+\sqrt[3]{n^3+6n}+n}+\frac{4}{1+\sqrt{1-\frac{4}{n}}}\right)=0+\frac{4}{1+1}=2\)
e/ \(lim\left(\frac{-3.3^n+4.4^n}{5.3^n+\frac{3}{2}.4^n}\right)=lim\left(\frac{-3\left(\frac{3}{4}\right)^n+4}{5.\left(\frac{3}{4}\right)^n+\frac{3}{2}}\right)=\frac{0+4}{0+\frac{3}{2}}=\frac{8}{3}\)
f/ \(lim\left(\frac{9^n-5.5^n+7.7^n}{9.3^n+5^n+2.8^n}\right)=lim\left(\frac{1-5.\left(\frac{5}{9}\right)^n+7\left(\frac{7}{9}\right)^n}{9.\left(\frac{1}{3}\right)^n+\left(\frac{5}{9}\right)^n+2.\left(\frac{8}{9}\right)^n}\right)=\frac{1}{0}=+\infty\)
g/ \(lim\left(\frac{6.6^n+3^5.9^n}{3^3.9^n-\frac{1}{2}.4^n}\right)=lim\left(\frac{6\left(\frac{2}{3}\right)^n+3^5}{3^3-\frac{1}{2}\left(\frac{4}{9}\right)^n}\right)=\frac{3^5}{3^3}=9\)
\\(\\lim\\limits_{x\\rightarrow-\\infty}\\left(2x^3-x^2+3x-5\\right)\\)
\n\n\\(\\lim\\limits_{x\\rightarrow2}\\frac{3}{\\left(x-2\\right)\\left(x^2-3x+2\\right)}\\)
\n\n\\(\\lim\\limits_{x\\rightarrow0}\\frac{x^2-5}{x^5+x^4}\\)
\n12/ lim\(\frac{3^n+5^{n+2}}{2.4^n+5^n}\)
13/ lim\(\left(\sqrt{n^4+3n+1}-n^2-1\right)\)
14/ lim\(\left(\sqrt[3]{n^2-n^3}+n\right)\)
15/ lim\(\frac{n^2+\sqrt[3]{1-n^6}}{\sqrt{n^4+1}-n^2}\)
tìm các giới hạn
a)lim(\(\sqrt{n+1}-\sqrt{n}\))
b)lim\(\left(\sqrt{n+5n+1}-\sqrt{n^2-n}\right)\)
c)lim\(\left(\sqrt{3n^2+2n-1}-\sqrt{3n^2-4n+8}\right)\)
d)lim\(\frac{2^n+6^n-4^{n+1}}{3^n+6^{n+1}}\)
e)lim\(\frac{3^n-4^n+5^n}{3^n+4^n-5^n}\)
f)lim\(\frac{1+3+5+.....+\left(2n+1\right)}{3n^2+4}\)
g)lim[\(\frac{1}{1.2}+\frac{1}{2.3}+....+\frac{1}{n\left(n+1\right)}\)]
h)lim\(\frac{1^2+2^2+3^2+.....+n^2}{n\left(n+1\right)\left(n+2\right)}\)
a/ \(=lim\frac{1}{\sqrt{n+1}+\sqrt{n}}=\frac{1}{\infty}=0\)
b/ \(=lim\frac{6n+1}{\sqrt{n^2+5n+1}+\sqrt{n^2-n}}=\frac{6+\frac{1}{n}}{\sqrt{1+\frac{5}{n}+\frac{1}{n^2}}+\sqrt{1-\frac{1}{n}}}=\frac{6}{1+1}=3\)
c/ \(=lim\frac{6n-9}{\sqrt{3n^2+2n-1}+\sqrt{3n^2-4n+8}}=lim\frac{6-\frac{9}{n}}{\sqrt{3+\frac{2}{n}-\frac{1}{n^2}}+\sqrt{3-\frac{4}{n}+\frac{8}{n^2}}}=\frac{6}{\sqrt{3}+\sqrt{3}}=\sqrt{3}\)
d/ \(=lim\frac{\left(\frac{2}{6}\right)^n+1-4\left(\frac{4}{6}\right)^n}{\left(\frac{3}{6}\right)^n+6}=\frac{1}{6}\)
e/ \(=lim\frac{\left(\frac{3}{5}\right)^n-\left(\frac{4}{5}\right)^n+1}{\left(\frac{3}{5}\right)^n+\left(\frac{4}{5}\right)^n-1}=\frac{1}{-1}=-1\)
f/ Ta có công thức:
\(1+3+...+\left(2n+1\right)^2=\left(n+1\right)^2\)
\(\Rightarrow lim\frac{1+3+...+2n+1}{3n^2+4}=lim\frac{\left(n+1\right)^2}{3n^2+4}=lim\frac{\left(1+\frac{1}{n}\right)^2}{3+\frac{4}{n^2}}=\frac{1}{3}\)
g/ \(=lim\left(\frac{1}{1}-\frac{1}{2}+\frac{1}{2}-\frac{1}{3}+...+\frac{1}{n}-\frac{1}{n+1}\right)=lim\left(1-\frac{1}{n+1}\right)=1-0=1\)
h/ Ta có: \(1^2+2^2+...+n^2=\frac{n\left(n+1\right)\left(2n+1\right)}{6}\)
\(\Rightarrow lim\frac{n\left(n+1\right)\left(2n+1\right)}{6n\left(n+1\right)\left(n+2\right)}=lim\frac{2n+1}{6n+12}=lim\frac{2+\frac{1}{n}}{6+\frac{12}{n}}=\frac{2}{6}=\frac{1}{3}\)
tìm \(lim\frac{1+\frac{2}{3}+\left(\frac{2}{3}\right)^2+...+\left(\frac{2}{3}\right)^n}{1+\frac{1}{5}+\left(\frac{1}{5}\right)^2+...+\left(\frac{1}{5}\right)^n}\)
Theo công thức tổng CSN:
\(1+\frac{2}{3}+...+\left(\frac{2}{3}\right)^n=\frac{1-\left(\frac{2}{3}\right)^{n+1}}{1-\frac{2}{3}}=3-3.\left(\frac{2}{3}\right)^{n+1}\)
\(1+\frac{1}{5}+...+\left(\frac{1}{5}\right)^n=\frac{1-\left(\frac{1}{5}\right)^{n+1}}{1-\frac{1}{5}}=\frac{5}{4}-\frac{5}{4}\left(\frac{1}{5}\right)^{n+1}\)
\(\Rightarrow lim\frac{3-3\left(\frac{2}{3}\right)^{n+1}}{\frac{5}{4}-\frac{5}{4}\left(\frac{1}{5}\right)^{n+1}}=\frac{3}{\frac{5}{4}}=\frac{12}{5}\)